Synthesıs and characterızatıon of organo modıfıed nanoclay / polyethylene terephthalate - Türk, Zeynep (My University, 2015)
ORGANO MODİFİYE NANOKİL/ POLİETİLEN TEREFTALAT (PET) KOMPOZİTLERİN SENTEZİ VE KARAKTERİZASYONU Kompozitler eşşiz ve daha üstün özelliklere sahip yeni maddeler oluşturmak için iki ya da daha fazla farklı maddelerin bir araya getirilmesiyle elde edilir. Polietilen Tereftalat (PET), dokumacılıktan lastiklerin güçlendirilmesine, meşrubat şişelerinden, paketlemeye geniş uygulama alanı bulmakta olan bu polimer, düşük maliyetli ve yüksek performanslı bir termoplastiktir. Kil; yüksek adsorpsiyon, düşük maliyet, yüksek iyon değişim kapasitesi, modifikasyona uygun oluşu, yüksek hacim oranı/ yüzey alanı, sahip olduğu şekil ve ülkemizde bol miktarda bulunduğundan dolayı farklı alanlarda kullanımı yaygın olan bir malzemedir. Bu çalışmamızda polimerik malzeme olan PET’e ve farklı yüzdeliklerde organo modifiye nanokil katkılanarak nanokompozit filmler, in-situ polimerizasyon metodu ile elde edilmiştir. Hazırlanan nanokompozitlerin kimyasal yapısı fourier transform infrared spektroskopisi (FTIR) ile karakterize edildi. Nanokompozitlerin yüzey morfolojileri taramalı elektron mikroskopu (SEM) ile incelendi. Termal özellikleri termogravimetrik analiz (TGA) ve diferansiyel taramalı kalorimetri (DSC) ile incelendi. Elde edilen sonuçlara göre yapılan değerlendirmede PET/ Organo modifiye nanokil kompozitlerinin termal kararlılıklarının PET’e göre daha iyi olduğu görülmüştür. Katkılanan PET’teki kil yüzdesi arttıkça kırılganlığının arttığı gözlenmiştir. Aynı zamanda katkı yüzdesi arttıkça yüksek kil yüzdeliklerinde kil yığınları oluşmakta ve bu da polimer-kil yüzey etkileşimini azaltmaktadır; çünkü yığınlar polimer matrisin kil tabakaları arasına girmesini engellemektedir.

SYNTHESIS AND CHARACTERIZATION OF ORGANO MODIFIED NANOCLAY/ POLYETHYLENE TEREPHTHALATE Composites are gained by gathering two or more different substances as to form new materials that is in possession of matchless and more compare properties. Polyethylene terephthalate (PET), which is found in large areas of usage, in the shape of weaving, fortification of synthetic rubbers, beverage bottles, packaging, is a kind of thermoplastic polymer that has high performance and low cost qualities. Clays are some sort of supplies that become common in several areas of use due to the fact that they have higher adsorption, low expenditure, superior capacity of ion alteration, modification suitability, high volume fraction / surface area, incompatible shape, and abound in Turkey. In this study, nanocomposite films, which work in PET that is a type of polymeric material, and work into modified organo-nanoclays with different percentages, obtained with the method called as in-situ polymerization. The chemical structures of nanocomposites prepared were investigated by fourier transform infrared spectroscopy (FT-IR). The surface morphologies of this nanocomposites were examined by scanning electron microscope (SEM). Their thermal properties were analyzed by differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). According to the results obtained, the thermal stabilities of modified nanoclay composites got better than PET. Besides, while the percent of clay in the doped PET was rising, its fragility increased. At the same time, high mass of clay formed when the percent of contribution developed. Thus, the surface interaction of polymer-clay decreased, because the composed aggregations prevented the polymer matrix from going into the layer of clay.
Keywords: Fizikokimya; Kimya, Fiziksel